Cinema on the cultural front: Film-making and the Mozambican revolution - Gray, Ros (Journal of African Cinemas, 2012)
During the armed struggle and the revolution that followed independence in Mozambique, film-making was understood as operating on the 'cultural front' of an international struggle against capitalist imperialism. Shortly after independence in 1975, FRELIMO established an Instituto Nacional de Cinema (the INC), and Maputo became a key site in a network of African liberationist film-making that had been emerging since the late 1960s. In a country in which most of the population had no prior experience of the moving image, cinema offered FRELIMO the possibility of mobilizing around a new identity based on revolutionary nationalism, and teaching the Mozambican people about how the radical transformations of decolonization connected them to other peoples struggling for emancipation across the world. This article explores how the moving image operated during the Mozambican revolution as an agent of social change, and how this involved decolonizing film-making itself – in all its modes of production, distribution and screening. In the offices of the Ebano film production house there is a black and white photograph. It shows a circle of young men, some with cameras, standing and kneeling for a group portrait. I recognize Licnio Azevedo, Camillo de Sousa and Joao Costa among them. The caption, in type-writer print, reads: 'Angola (Cahama) – Setembro 1981'. I ask Camillo about the photograph. He tells me how he, Licínio and Funcho came to be in Angola. They went at the time of the South African invasion and spent several weeks in trenches under fire working with the film-makers in the photograph to make Cinco Tiros de Mauser. Camillo points to them one by one: 'That one, Carlos Henriques, he died. Funcho made Pamberè ne Zimbabwe with him – the first Southern African film made without foreign support. We wanted to show that it was the same fight we were involved with together against Apartheid. This is something important that you should know. Our struggle wasn't about nationalism. It may sound strange these days, but their struggle was our struggle too.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qYWMuMy4yLjEzOV8x